Evaluation of Butterfly Pea (Clitoria ternatea) Extract with Different Ethanol-Water Solutions for Potential Natural Colorant Indicator - Abdullah, Nor Adilah; Hean, Chong Gun; Azman, Ezzat Mohamad; Zainal Abedin, Nur Hanani (Food Science and Engineering, 2025)
Dried Butterfly Pea (DBP) flowers were subjected to extraction using different concentrations of ethanol in water (0, 30, 50, 70, and 100%) through agitation in a water bath. The Total Phenolic Content (TPC), Total Flavonoid Content (TFC), Total Monomeric Anthocyanin Content (TMAC), antioxidant and antimicrobial properties, color, and pH sensitivity of the extracts were then evaluated. All extracts possessed antioxidant properties and showed potential antimicrobial activity. The highest TPC and TMAC were observed for the DBP extract in 30% ethanol, at 58.55 mg GAE/g d.w. and 3.53 mg/g d.w. of extract, respectively (p < 0.05). The 30% ethanol extract had the highest sensitivity to pH changes compared to the 100% ethanol extract. The findings of this study indicate that BP extracted with 30% ethanol has the potential to be used as a natural food dye.